Salting effects on protein components in aqueous NaCl and urea solutions : toward understanding of urea-induced protein denaturation - Mu, Yuguang (2013)
The mechanism of urea-induced protein denaturation is explored through studying the salting effect of urea on 14 amino acid side chain analogues, and N-methylacetamide (NMA) which mimics the protein backbone. The solvation free energies of the 15 molecules were calculated in pure water, aqueous urea, and NaCl solutions. Our results show that NaCl displays strong capability to salt out all 15 molecules, while urea facilitates the solvation (salting-in) of all the 15 molecules on the other hand. The salting effect is found to be largely enthalpy-driven for both NaCl and urea. Our observations can explain the higher stability of protein’s secondary and tertiary structures in typical salt solutions than that in pure water. Meanwhile, urea’s capability to better solvate protein backbone and side-chain components can be extrapolated to explain protein’s denaturation in aqueous urea solution. Urea salts in molecules through direct binding to solute surface, and the strength is linearly dependent on the number of heavy atoms of solute molecules. The van der Waals interactions are found to be the dominant force, which challenges a hydrogen-bonding-driven mechanism proposed previously.